Risk of neuroblastoma and residential proximity to industrial and urban sites: A case-control study. (July 2016) - García-Pérez, Javier; Morales-Piga, Antonio; Gómez-Barroso, Diana; Tamayo-Uria, Ibon; Pardo Romaguera, Elena; Fernández-Navarro, Pablo; López-Abente, Gonzalo; Ramis, Rebeca
Abstract: Background: Neuroblastoma is the most common extracranial solid tumor in children but its etiology is not clearly understood. While a small fraction of cases might be attributable to genetic factors, the role of environmental pollution factors needs to be assessed. Objectives: To ascertain the effect of residential proximity to both industrial and urban areas on neuroblastoma risk, taking into account industrial groups and toxic substances released. Methods: We conducted a population-based case-control study of neuroblastoma in Spain, including 398 incident cases gathered from the Spanish Registry of Childhood Tumors (period 1996–2011), and 2388 controls individually matched by year of birth, sex, and region of residence. Distances were computed from the respective subject's residences to the 1271 industries and the 30 urban areas with ≥ 75, 000 inhabitants located in the study area. Using logistic regression, odds ratios (ORs) and 95% confidence intervals (95%CIs) for categories of distance (from 1 km to 5 km) to industrial and urban pollution sources were calculated, with adjustment for matching variables and socioeconomic confounders. Results: Excess risk (OR; 95%CI) of neuroblastoma was detected for the intersection between industrial and urban areas: (2.52; 1.20–5.30) for industrial distance of 1 km, and (1.99; 1.17–3.37) for industrial distance of 2 km. By industrial groups, excess risks were observed near 'Production of metals' (OR = 2.05; 95%CI = 1.16–3.64 at 1.5 km), 'Surface treatment of metals' (OR = 1.89; 95%CI = 1.10–3.28 at 1 km), 'Mines' (OR = 5.82; 95%CI = 1.04–32.43 at 1.5 km), 'Explosives/pyrotechnics' (OR = 4.04; 95%CI = 1.31–12.42 at 4 km), and 'Urban waste-water treatment plants' (OR = 2.14; 95%CI = 1.08–4.27 at 1.5 km). Conclusions: These findings support the need for more detailed exposure assessment of certain substances released by these industries. Highlights: We studied risk of neuroblastoma near Spanish industries and urban sites We used logistic regression models in a population-based case-control study We found excess risk in the intersection between industrial and urban areas Risk also was found near metal industries, mines, pyrotechnics and sewage plants The findings support the need for more detailed exposure assessment